2022
DOI: 10.1002/ece3.9432
|View full text |Cite
|
Sign up to set email alerts
|

Tooth marker of ecological abnormality: The interpretation of stress in extinct mega herbivores (proboscideans) of the Siwaliks of Pakistan

Abstract: Climate affects living ecosystems and defines species physiology. Climate change causes certain stress on animals, recorded as Enamel Hypoplasia (EH). Proboscideans, the mega herbivores, were extensively represented in the Siwaliks of Pakistan between the Middle Miocene to Pleistocene (~15.99–~0.6 Ma). This study was carried out on 15 species from 9 genera and 4 families using 319 teeth from 266 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 114 publications
0
0
0
Order By: Relevance
“…A paleontological study confirmed that adaptation to grazing lifestyles could be detected in late gomphotheres, a proboscidean taxon that went extinct in the late Pleistocene [58]. However, another study highlighted that proboscidean fossils from the middle Miocene to the late Pleistocene showed enamel hypoplasia, which can be regarded as a sign of chronic stress, though the reason cannot be specified [59].…”
Section: The Fall Of the Proboscideans And The Dawn Of The Ruminantsmentioning
confidence: 96%
“…A paleontological study confirmed that adaptation to grazing lifestyles could be detected in late gomphotheres, a proboscidean taxon that went extinct in the late Pleistocene [58]. However, another study highlighted that proboscidean fossils from the middle Miocene to the late Pleistocene showed enamel hypoplasia, which can be regarded as a sign of chronic stress, though the reason cannot be specified [59].…”
Section: The Fall Of the Proboscideans And The Dawn Of The Ruminantsmentioning
confidence: 96%